Rapid Micropropagation of Lemon Verbena (Lippia citriodora L.) Using In vitro Culture - A Oladzad; A Qaderi; H Naghdi Badi; AR Zare (Institue of Medicinal Plants, ACECR, 2012)
Background: The genus Lippia contains more than 200 species that Lemon verbena (Lippia citriodora) has a high medicinal value. Therefore expansion of its acreage using development of rapid and new propagation methods has a high importance. Objective: The aim of this study was to present a rapid, new and effective method, using nodal segments, for large scale propagation of this plant. Methods: In order to the shoot micropropagation, lateral buds on nodal segments were placed on MS medium supplemented with different concentrations of auxin and cytokinin hormones. Root induction was studied in the media containing IBA, NAA and activated charcoal. For acclimatization, plants were transferred to plastic bags containing a mixture of vermiculite, perlite and soil. Results: The highest number of shoots was obtained on the MS medium supplemented with 3 mg/L BAP in combination with 0.1 mg/L IBA and well-developed shoots were rooted on the MS medium with 0.5 mg/L IBA and 2 gr/L activated charcoal. Conclusion: According to the high rate of proliferation in the media supplemented with BAP and IBA (3 and 0.1 mg/L, respectively), this technique can be used instead of conventional propagation methods, as a quick and economical technique to propagation of a wide range of the same plants.